PUSH AND PULL FACTORS INFLUENCING INDONESIAN YOUTHS’ INTENTION TO WORK IN AUSTRALIA: THE MODERATING ROLE OF CAREER ADAPTABILITY - Hendi Hadinata Wongso; Efa Irdhayanti; Harry Setiawan; Ilzar Daud; Ikram Yakin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The intention of Indonesian youth to work abroad, particularly in Australia, has continued to increase. This phenomenon is influenced by push factors in the home country, such as limited job opportunities and high unemployment rates, as well as pull factors from the destination country, including opportunities for international experience, higher wages, and better career prospects. This research aims to explain the effects of push factors and pull factors toward the intention to work abroad to Australia among Indonesian youth, with career adaptability as a moderating variable. Adopting a quantitative design supported by a survey technique, involving 150 respondents aged 18–30 years selected through purposive sampling (Hair et al., 2019). Data were collected using a Likert-scale questionnaire and subsequently examined through Partial Least Squares Structural Equation Modeling (PLS-SEM) employing SmartPLS software. The analytical procedure comprised assessment of the measurement model (including convergent validity, discriminant validity, and construct reliability) as well as evaluation of the structural model (R², Q² predictive relevance, and path coefficients). The analysis confirms a significant positive effect of push and pull factors on the intention to work abroad. However, career adaptability does not moderate these relationships, suggesting that structural conditions and external opportunities play a more dominant role than individual career adaptability.